2020
DOI: 10.1101/2020.04.23.053322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sorcin stimulates Activation Transcription Factor 6α (ATF6) transcriptional activity

Abstract: Word count: 5222List of abbreviations: ATF6, activating transcription factor 6; BiP, binding immunoglobulin protein; CHOP, C/EBP homologue protein; ChREBP, Carbohydrate Responsive Element Binding Protein; DTT, dithiothreitol; ER, endoplasmic reticulum; FFA, free fatty acids; GRP78, glucose-regulated protein 78; HFD, high fat diet; MEF, mouse embryonic fibroblast; NEFA, nonesterified fatty acid; NFAT, nuclear factor of activated T-cells; RIP, rat insulin promoter; RyR, ryanodine receptor; SERCA, sarco/endoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…When ER stress occurs in a cell that results in sorcin (a Ca 2+ -binding protein that helps to maintain Ca 2+ homeostasis in ER) dysfunction, it also increases the ATF6 activity, which results in the advancement of insulin dysfunction, obesity, and type II diabetes [ 59 ]. Obesity and type II diabetes are associated with high-fat and high-glucose concentrations, which lead to beta-cell dysfunction in the pancreas via ATF6 [ 60 ].…”
Section: Discovery and Investigation Of The Er Stress Mechanismmentioning
confidence: 99%
“…When ER stress occurs in a cell that results in sorcin (a Ca 2+ -binding protein that helps to maintain Ca 2+ homeostasis in ER) dysfunction, it also increases the ATF6 activity, which results in the advancement of insulin dysfunction, obesity, and type II diabetes [ 59 ]. Obesity and type II diabetes are associated with high-fat and high-glucose concentrations, which lead to beta-cell dysfunction in the pancreas via ATF6 [ 60 ].…”
Section: Discovery and Investigation Of The Er Stress Mechanismmentioning
confidence: 99%
“…Also, [72] reported that ATF-6 activation via ER stress-induced cell death and inflammation was alleviated on treatment with miR-149. When ER stress occurred in a cell that results in sorcin ( a Ca 2+ binding protein that helps to maintain Ca 2+ homeostasis in the ER) dysfunction, it also leads to an increase in the activity of ATF6, which results in the advancement of insulin dysfunction, obesity, and type II DM [73]. Obesity and type II diabetes are associated with high-fat and high glucose concentrations, which lead to β-cells dysfunction via the ATF6 [74].…”
Section: The Evolution and Prospect Of The Er Stress Mechanismmentioning
confidence: 99%